A study on enthalpy exchanger with modified functional layers based on chloride. (2nd January 2017) - Zhang, Chuanyu; Xu, Jingcui; Ge, Tianshu; Dai, Yanjun; Wang, Ruzhu
Abstract : In order to improve the supply air quality, more and more investigations have been conducted on enthalpy exchanger (or total heat exchanger). Enthalpy exchanger consists of functional layers and support layers. The functional layers, which exchange the heat and moisture between fresh air and exhausted air, play a critical role in improving efficiencies of the exchanger. A paper matrix with low cost and easy fabrication is widely used as the functional layers in current enthalpy exchangers. In this study, modified paper by spraying calcium chloride solution is proposed to improve the hygroscopicity of conventional material. Novel functional layers with different solution concentrations of 5, 10, 20, 30, and 40% are fabricated and analyzed. Performance of exchangers made by the modified functional layers and by original layers are tested and compared. Results show that when airflow velocity is 0.3 m/s (corresponding to 50 m 3 /h), sensible efficiency, latent efficiency, and enthalpy efficiency of modified enthalpy exchanger with use of 30% solution increase from 62, 44, and 49% to 75, 69, and 71% in the winter conditions and from 53, 51, and 52% to 75.8, 71.5, and 73% in the summer conditions compared with original exchanger, the increasing of pressure drop caused by treatment can be ignored. Besides, application of the modified enthalpy exchanger is tested and it is proven that the modified exchanger can obtain better performance compared with original exchanger.